Transparansi Dan Akuntabilitas Pengelolaan Dana Desa Dalam Pemaknaan Masyarakat Desa Secara Kualitatif - Setyawati, Vincentia Devina; Yoseph Yustinianus Ferdinand, Deograsias (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2020)
The administration of the village government obtained an allocation of village funds since the enactment of Law Number 6 of 2014 concerning Villages. One of the village's income comes from the allocation of village funds that are part of the district/city balance fund. Therefore, the management of village funds should refer to the principle of managing state finances so they must be managed with the principles of transparency and accountability. Therefore, this study will analyze the community's understanding of transparency and accountability in the management of village fund finances, especially in the "X" Village, Malang Regency. This research uses a qualitative approach with ethnographic methods. Data collection techniques in this research are field studies and literature studies to obtain a picture of the interpretation of the values ​​of transparency and accountability and secondary data is data obtained in the form of processed from the village government. This research shows that the villagers actually interpret transparency and accountability not with high transparency standards. The community emphasizes the mutual cooperation side in realizing transparency through the participation of all elements of the village in managing village funds.